The Effect Of Auditor Competence On Audit Quality With Auditor Independence As A Mediation Variable At The Medan City Inspectorate - Reni Vadia; Oktarini Khamilah Siregar; Dito Aditia Darma Nasution (International Journal of Management, Economic and Accounting, 2025)
This study aims to examine the influence of auditor competence on audit quality with auditor independence as a mediation variable at the Medan City Inspectorate. Auditor competence is seen as a combination of education, training, work experience, and analytical skills that are believed to improve the quality of internal audits in the public sector. The results of the study show that auditor competence has a positive and significant effect on audit quality. In addition, competence has also been shown to significantly increase auditor independence, which shows that competent auditors are better able to maintain objectivity and be free from pressure from other parties. Other findings revealed that auditor independence has a positive and significant influence on audit quality, confirming the important role of independence in maintaining the integrity and credibility of audit results. However, auditor independence has not been shown to play a significant role as a mediator in the relationship between audit competence and quality. Thus, the influence of competence on audit quality tends to be direct. These results have important implications for strengthening the role of the Inspectorate in the internal supervision of local governments through improving the professional competence of auditors and strengthening the protection system for their independence.